2016
DOI: 10.7287/peerj.preprints.2444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary analysis of vision genes identifies potential drivers of visual differences between giraffe and okapi

Abstract: Background. The capacity of species to respond and perceive visual signal is integral to their evolutionary success. Giraffe is closely related to okapi, but the two species have broad range of phenotypic differences including their visual capacities. Vision studies rank giraffe's visual acuity higher than all other artiodactyls despite sharing similar vision ecological determinants with most of them. To what extent giraffe unique visual capacity and its difference with okapi is reflected by changes in their v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…One study investigated the genetic mechanisms underlying giraffe's excellent visual abilities. Giraffes were found to have genes CRYAA and OPN1LW divergent from other ruminants (Ishengoma et al ., ). Specifically, sequence analysis of OPN1LW showed that one of the sites that affects spectral sensitivity of the red pigment is uniquely divergent between giraffes and other ruminants (Ishengoma et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One study investigated the genetic mechanisms underlying giraffe's excellent visual abilities. Giraffes were found to have genes CRYAA and OPN1LW divergent from other ruminants (Ishengoma et al ., ). Specifically, sequence analysis of OPN1LW showed that one of the sites that affects spectral sensitivity of the red pigment is uniquely divergent between giraffes and other ruminants (Ishengoma et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In Kruger National Park, South Africa, for instance, zebras were found to have a lower vigilance (by two‐thirds) when in the presence of giraffes than when in the presence of wildebeest ( Connochaetes taurinus ; Schmitt et al ., ). Recent genetic investigations implicate disparity in giraffe pelage patterns across subspecies as one of the factors causing isolation among giraffe subspecies due to pelage‐based mate choices (Brown et al ., ; Ishengoma et al ., ). These findings merit further investigation of the role of visualization in the intra‐ or interspecific social interactions of giraffes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[4,19,21]. Adaptive evolution of the vision genes facilitated by positive selection was widely reported in many other animals which rely on vision in dim-light environments, such as mole rats [25], Chinese forest musk deer [10], okapi [26], bats [11], and owls [27], although the positively selected genes varied cross species. Similar to these findings, 16 vision genes were found to undergo positive selection in N. nycticorax, suggesting that positive selection has played an important role in the adaptive evolution of the vision genes and thereby contributed to the morphological or functional modifications of the eyes favoring night vision.…”
Section: Discussionmentioning
confidence: 98%
“…Only then the animals detected the researcher and started the emission of hisses. The researcher could see the giraffe heads through the branches against the bright sky, whereas the giraffes, despite their acute vision [ 51 ], could hardly see the researcher when looking from bright sunlight towards the dense foliage. Probably, the hissing was triggered by the sudden detection of human smell just underneath their food source, as the olfactory abilities of giraffes are good [ 52 ].…”
Section: Main Textmentioning
confidence: 99%